Analisis Yuridis terhadap Kendala dalam Implementasi Pelaksanaan Kerja Sama Daerah di Kabupaten Sumenep - Mohamad Faishal Agil; Ansori Ansori (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Regional cooperation agreements are not something new, these regional cooperation agreements have a positive impact in improving people's welfare which makes this cooperation based on considerations of efficiency and effectiveness of public services that are mutually beneficial. In practice, there are problems that often arise in regional cooperation agreements. In this research, we want to examine in more depth the flow of implementing regional cooperation agreements and also want to examine what factors cause the failure or non-performance of a regional cooperation agreement with the Sumenep Regency Government. The results of this research are that the stages in regional cooperation agreements are regulated in Minister of Home Affairs Regulation No. 22 of 2020 article 6. And the problems that often arise are 1) The cooperation agreement that will be carried out is not accompanied by a draft of a mutual agreement between the regent and the leadership of the party that will collaborate. 2) Most of the articles on rights and obligations as well as financing have not found common ground so that the draft text of the cooperation agreement that has been discussed has not yet been signed. 3) The draft cooperation agreement that was prepared several times is not in accordance with the Minister of Home Affairs Regulation on Procedures for Regional Cooperation with Other Regions and Regional Cooperation with Third Parties.